Analysis on low velocity impact damage of laminated composites toughened by structural toughening layer. Issue 7 (22nd July 2015) - Sun, Xiaochen; Qu, Peng; Liu, Gang; Yi, Xiaosu; Su, Hao; Jia, Yuxi
Abstract : The intralaminar and interlaminar damages of U3160/3266 laminated composites toughened by polyamide nonwoven fabric (PNF) under low velocity impact are investigated through a numerical model which considers both the three‐dimensional continuum damage mechanics (CDM) and the bilinear cohesive zone model (CZM). The analysis of the intralaminar damage is implemented by the ABAQUS/Explicit finite element code coupled with a user‐defined subroutine VUMAT where the longitudinal failure, transverse matrix cracking, and nonlinear shear of the material are taken into account. Then the effects of the thickness and strength of PNF/3266 interlayer on the damage of composites are numerically analyzed. The results reveal that damage morphology can be simulated qualitatively compared to the experimental counterparts. With the decreasing interlayer thickness or the increasing interlayer strength, the damage area is effectively reduced. This work provides an effective model to predict the low velocity impact damage of composites, and is helpful for the optimization of interlayer toughened composites. POLYM. COMPOS., 38:1280–1291, 2017. © 2015 Society of Plastics Engineers